2020
DOI: 10.3390/ijerph17030808
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enablers of Health Service Utilisation for Childhood Skin Infections in Remote Aboriginal Communities of Western Australia

Abstract: In Australia, children living in remote Aboriginal communities experience high rates of skin infections and associated complications. Prompt presentation to primary care health services is crucial for early diagnosis and treatment. We performed a qualitative study in four remote Aboriginal communities in the Pilbara region of Western Australia to explore factors that affected health service utilisation for childhood skin infections in this setting. The study consisted of semistructured interviews and focus gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(70 citation statements)
references
References 39 publications
0
70
0
Order By: Relevance
“…This resonates with a recently published study on barriers and enablers to skin sore treatment in the Pilbara, which found that shyness, shame, fear of judgement, normalisation and prejudice were significant factors in the decision to seek care. 34 Primary healthcare staff in this eDelphi study, and in the Pilbara study, identified health promotion as a priority to increase health seeking for skin sores. 34 However, a number of participants discussed the risk of inadvertently increasing stigma if skin sores were associated with poor hygiene in health promotion activities.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This resonates with a recently published study on barriers and enablers to skin sore treatment in the Pilbara, which found that shyness, shame, fear of judgement, normalisation and prejudice were significant factors in the decision to seek care. 34 Primary healthcare staff in this eDelphi study, and in the Pilbara study, identified health promotion as a priority to increase health seeking for skin sores. 34 However, a number of participants discussed the risk of inadvertently increasing stigma if skin sores were associated with poor hygiene in health promotion activities.…”
Section: Discussionmentioning
confidence: 84%
“…34 Primary healthcare staff in this eDelphi study, and in the Pilbara study, identified health promotion as a priority to increase health seeking for skin sores. 34 However, a number of participants discussed the risk of inadvertently increasing stigma if skin sores were associated with poor hygiene in health promotion activities. A strong message from community is to prioritise a strengths-based approach to health promotion.…”
Section: Discussionmentioning
confidence: 84%
“…However, the strengths were the qualitative approach, which helped with the understanding of a complex situation, and the fact that the same participants would be those who participate in the educational phase of this project. Through the model proposed by Andersen [7,8], the conceptualization of need, enabling, and predisposing factors was described providing a framework on which to design future educational strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Andersen's base conceptual model of health service utilization was applied [7,8] for the analysis and for structuring the results. This model proposed three major factors that affected the access to health services: predisposing factors (demographic, social, economic, and cultural factors); enabling resources that influenced health service utilization, such as social relationships, community, and healthcare system characteristics; and needs, as perceived by the different actors.…”
Section: Designmentioning
confidence: 99%
“… 48 49 54 There are barriers to accessing Indigenous healers, traditional care providers, 41 and traditional medicine, 53 which healthcare providers tend to dismiss. 54 Families also experienced difficulties accessing information in their preferred language 46–48 and a lack of acknowledgement of the spiritual and emotional aspects of care. 48 …”
Section: Barriersmentioning
confidence: 99%